# Table of Derivatives In this table, u and v represent functions of x (u(x) and v(x)); a, n, e represent constants (e = 2.7183 ...). d (x) = 1 dx du dv d (u ± v ± ...) = ± ± ...

dx dx dx d (a) = 0 dx du d (au) = a dx dx d du dv (uv) = v +u dx dx dx v du − u dv d u ( ) = dx 2 dx dx v v 1 du d 1 ( )=− 2 dx u u dx d n du (u ) = nun−1 dx dx loga e du d (loga u) = dx u dx d 1 du (ln u) = dx u dx du d u (a ) = au ln a dx dx d u du (e ) = eu dx dx Another rule to learn is the Chain Rule. Deﬁne a function y = f (u). In such case, the Chain Rule indicates that d df du (y) = . dx du dx Take the case where y is deﬁned such that y = f (u(v)). In this case, the Chain Rule indicates that df du dv d (y) = . dx du dv dx Let me give you an example of the application of the Chain Rule. Say f (u) = u − 1, u(v) = v 2 and v(x) = 2x + 1. Therefore y = f (x) = f (u(v(x))). Plugging the numbers in the example, we ﬁnd that y = (2x + 1)2 − 1. See that dy = 2(2x + 1)2 = 4(2x + 1). dx Now see that applying the Chain Rule du dv d (y) = 1 ∗ ∗ dx dv dx d dv (y) = 1 ∗ 2v ∗ dx dx d (y) = 1 ∗ 2v ∗ 2. dx
d Plug v into the equation and see that dx (y) = 4(2x + 1). This exactly the same result as substituting in all the values at the beginning and taking a derivative with respect to x.

1